Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21037/fomm-21-45
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of heterogeneous graft presentations in bone reconstructions during sinus lift elevation surgery: an immunolabeling and histomorphometric study performed in rabbits

Abstract: Background: This study aims to analyze the process of bone formation, maturation and mineralization promoted by Cerabone ® functionalization with raloxifene in rabbit sinus floor elevation, through immunohistochemical and histomorphometric analyses.Methods: Twenty-four male rabbits had their maxillary sinuses filled. To access the sinus cavity a circular window with a diameter of 5 mm was made bilaterally to the midline of the nasal dorsum, the sinus membrane was detached and elevated using special curettes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In contrast, building on previous research [ 35 ], it is interesting to observe that the effectiveness of Raloxifene in promoting bone growth might vary depending on the context. A prior study by our team, using a different xenograft, found a 20% improvement in bone formation with Raloxifene, especially over an extended 42-day healing period.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, building on previous research [ 35 ], it is interesting to observe that the effectiveness of Raloxifene in promoting bone growth might vary depending on the context. A prior study by our team, using a different xenograft, found a 20% improvement in bone formation with Raloxifene, especially over an extended 42-day healing period.…”
Section: Discussionmentioning
confidence: 95%
“…During image acquisition, the calibrated analyzer performed the histological description in each of the groups following previous studies of the research group. The images (4× magnification) were exported to Adobe Photoshop (Adobe Systems, version CC 2017, San Jose, CA, USA) and were merged to make a panoramic image and perform a descriptive analysis [ 41 ].…”
Section: Methodsmentioning
confidence: 99%